الهجمات السييرانية: مفهومها والمسؤولية الدولية الناشئة عنها في ضوء التنظيم الدولي المعاصر - الفتلاوي، أحمد عبيس نعمة (جامعة بابل - كلية القانون, 2016)
يشهد العالم في الفترة الراهنة نوعا جديدا من سباق التسلح، لا على غرار المعروفة منها في حفل الأسلحة التقليدية وغير التقليدية، ويقوم هذا السباق على استحداث أو تطوير برامج إلكترونية معدة لأغراض عسكرية تعرف اختصاراً بالسايبر (Cyber). لقد بدأ الباحثون منذ مدة لا تتجاوز خمس سنوات ماضية بالبحث والتحليل القانوني على هذا الموضوع. في ضوء معطيات مؤكدة بأن تهديداً ستتسبب به الهجمات السيبرانية على صعيد السلم والأمن الدوليين وبمستوى لا يقل جسامة عن أخطر التهديدات المعروفة دولياً.
In the current period the world is witnessing, a new kind of arms race, not the well-known ones in conventional and non-conventional weapons field style, this race is based on the development of electronic programs intended for military purposes know as Cyber race. Researchers have since begun a period not exceeding five years ago the legal research and analysis on this topic, in the light of the data confirmed that the threat would cause its cyber attacks at the level of international peace and security and the level of at least the most serious threats for the gravity of the internationally known. And because the subject occupies a leading position in the legal effort, particularly when specialized international institutions on the one hand, and the lack of Arab and Iraqi ones in particular research on the other hand, these two facts paid to choice it and to be the subject of this study, dependents in analysis of the provisions of the Public International Law and related to the conventions which organization to use international efforts prohibition or restriction, as well as the most important judicial and jurisprudence, which addressed the issue of cyber attacks from different sides. That a number of questions would be raised at the research and analysis on the subject of the study like: What are the cyber attacks and hwo originated in accordance to Public international law? You could be classified within the means and methods of fighting? And if so do you apply the provisions of international conventions and customary rules related to the conduct of combat operations? On the other hand, how the international community deal with the legal vacuum which witnessed the subject of international regulation of cyber problem? And is a glimmer of hope from the start of multilateral or bilateral international negotiations to end the controversy about the legitimacy of resorting to it in light of the provisions of international humanitarian law and customary rules of stable between civilized nations? And what if the failure of the international community continued to arrive at the conclusion of an international convention on organized cyber military purposes? The key to the solution lies in the intervention of the leading IT countries, particularly the United States, Russia, China or other countries to interfere with the convergence of views? All of these problems we will try to answer in the light of the research plan divided on two sections: the first shed the light on the concept of cyber attacks, in terms of the word Cyber source in the language and terminology, as well as browse the date on which began using electronic means to this body armed attacks on the one hand. On the other hand we will look at the most prominent models cyber documented by formal and informal institutions, which would give a chance for the fact that the use of electronic technology in the military and security field and identify future implications for international peace and security. The second section will focus on the contemporary international regulation of cyber attacks, in the light of the principles of the right to resort to war (Jus in bellum) and the behavior ofWar ((Jus ad Bello. Whether resorting to cyber prohibited or restricted in accordance with the provisions of international law and humanitarian in particular, we will look to emerging about the international responsibility in light of the current international regulation, as well as research and analysis in the international effort on the conclusion of a multilateral international convention prohibiting or restricting mail use for military purposes in comparison with national legislation to combat cyber crime like Convention of the Council of Europe in 2001 known (Convention against Cyber crimes).
Keywords: التنظيمات السياسية -- الأحزاب السياسية -- البرامج الإلكترونية -- الوسائل الإلكترونية -- السايبر -- التنظيم الدولي المعاصر -- المجتمع الدولي -- مستخلصات الأبحاث